Storage stability study of chocolate flavored fresh milk processed by Iloilo Federation of Dairy Cooperatives in Tigbauan, Iloilo - Gerez, Ma. Leah Magturo
Four flavored (4) fresh milk (chocolate, ube, mango, and melon) processed by Iloilo Federation of Dairy Cooperatives were subjective to ranking for preferenceby Grade six pupils and High School students.